Pengaruh Kompetensi Dan Lingkungan Kerja terhadap Kinerja Pegawai melalui Kepuasan Kerja sebagai Variabel Intervening - Maya Sari (Journal of Business and Economics (JBE) UPI YPTK, 2022)
This study aims to determine the effect of competence and work environment on employee performance through job satisfaction as intervening variable at the Center for Quality Assurance of Education in West Sumatra Province. The sample in this study was taken using the saturated sample method (census) at the Center for Quality Assurance of Education in West Sumatra Province. The number of samples used as many as 76 people. The analytical method used is Structral Equation Modeling (SEM) Analysis with Partial Least Square (PLS). To test the hypothesis, the Path Coefficient is used, which is a test carried out to see the direct effect and the Indirect Effect is a test that aims to see the indirect effect. The results of this study indicate that: 1) Competence has a positive and insignificant effect on job satisfaction at BBPMP West Sumatra Province, 2) Work environment has a positive and significant effect on job satisfaction at BBPMP West Sumatra Province. 3) Competence has a positive and significant effect on employee performance at BBPMP West Sumatra Province. 4) The work environment has a negative and insignificant effect on employee performance at BBPMP West Sumatra Province. 5) Job satisfaction has a positive and significant effect on employee performance at BBPMMP West Sumatra Province. 6) Job Satisfaction mediates the effect of competence on employee performance at BBPMP West Sumatra Province. 7) Job satisfaction does not mediate the effect of the work environment on employee performance at BBPMP West Sumatra Province